At immature mossy fibers-CA3 connections, activation of presynaptic GABAB receptors by endogenously released GABA contributes to synapses silencing - Safiulina, Victoria F.; Cherubini, Enrico (Frontiers in Cellular Neuroscience, 2009)
Early in postnatal life correlated GABAergic activity in the hippocampus is thought to play a crucial role in synaptogenesis and in the development of adult neuronal networks. Unlike adulthood, at this developmental stage, mossy fibers (MF) which are the axons of granule cells, release GABA into CA3 principal cells and interneurons. Here, we tested the hypothesis that at MF-CA3 connections, tonic activation of GABAB autoreceptors by GABA is responsible for the low probability of release and synapse silencing. Blocking GABAB receptors with CGP55845 enhanced the probability of GABA release and switched on silent synapses while the opposite was observed with baclofen. Both these effects were presynaptic and were associated with changes in paired-pulse ratio and coefficient of variation. In addition, enhancing the extracellular GABA concentration by repetitive stimulation of MF or by blocking the GABA transporter GAT-1, switched off active synapses, an effect that was prevented by CGP55845. In the presence of CGP55845, stimulation of MF induced synaptic potentiation. The shift of EGABA from the depolarizing to the hyperpolarizing direction with bumetanide, a blocker of the cation-chloride co-transporter NKCC1, prevented synaptic potentiation and caused synaptic depression, suggesting that the depolarizing action of GABA observed in the presence of CGP55845 is responsible for the potentiating effect. It is proposed that, activation of GABAB receptors by spillover of GABA from MF terminals reduces the probability of release and contributes to synapses silencing. This would act as a filter to prevent excessive activation of the auto-associative CA3 network and the emergence of seizures.